Eﬀect of stabilizer pressure biofeedback on post-thyroidectomy neck pain in postmenopausal women: a randomized controlled trial - Hassan, Elham S.; Botla, Afaf M.; Abdou, Marian Y.; Attalla, Abdel Hamid A.; Ali, Khadra Mohamed; Aboelmaged, Shreen Rashad (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. To investigate the eﬀect of stabilizer pressure biofeedback on post-thyroidectomy neck pain, disability, endurance capacity of deep cervical ﬂexors (DCFs), and cervical range of motion (ROM) in women after menopause.Methods. Thirty-six women aged 50–65 years with post-thyroidectomy neck pain were incorporated in this study. Participants were assigned randomly into two groups. Each group was comprised of 18 women. Group A underwent active stretching exer-cises of the neck muscles. Group B underwent cranio-cervical ﬂexion training using stabilizer pressure biofeedback in addition to active stretching exercises. Q1: The treatment interventions were administered 3 times per week for six weeks. A stabilizer pressure biofeedback device was utilized to evaluate the endurance capacity of the DCFs. A digital goniometer was used to measure the cervical spine ROM. The Neck Pain and Disability Scale (NPDS) was utilized to assess neck pain and disability levels prior to and following six weeks of treatment.Results. Group A had no signiﬁcant improvement over group B in the endurance capacity of the DCFs. Both groups (A and B) showed signiﬁcant increases in cervical ROM and decreases in NPDS. However, comparing the two groups post-treatment, group B showed a statistically signiﬁcant improvement in all outcome measurements.Conclusions. Stabilizer pressure biofeedback is eﬃcacious in enhancing the endurance of DCFs and ROM, in addition to reducing neck pain and disability in postmenopausal women who experience neck pain after thyroidectomy.
Keywords: mastectomy; breast neoplasms; scar tissue; myofascial treatment; range of motion; muscle elasticity